Aromatic polyesters containing pendant azido groups: synthesis, characterization, chemical modification and thermal cross-linking - Nagane, Samadhan S.; Verma, Savita; Tawade, V, Bhausaheb; Sane, Prakash S.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (European Polymer Journal, 2019)
A partially bio-based bisphenol containing pendant azido group viz., 4,4'-(5-azidopentane-2,2-diyl) diphenol (AZBPA) was synthesized starting from 4,4'-bis (4-hydroxyphenyl) pentanoic acid. AZBPA was reacted with isophthaloyl chloride (IPC), terephthaloyl chloride (TPC) and a mixture of IPC/TPC (50:50 mol%) by phase transfer-catalyzed interfacial polycondensation route to obtain aromatic polyesters containing pendant azido groups. Copolyesters containing pendant azido groups were also synthesized by polycondensation of different molar proportions of AZBPA and commercially available 4,4'-(1-phenylethane-1,1-diyl) diphenol (BPA-AP) with IPC. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.85-1.64 dL/g and 58,900-190,400, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. X-Ray diffraction analysis showed that (co)polyesters were amorphous in nature. (Co)polyesters were characterized using FT-IR, H-1 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolyester containing pendant azido groups was carried out quantitatively using copper-catalyzed azide-alkyne cycloaddition (CuAAC) with two alkynes viz., phenyl acetylene (PA) and ethynyl-4-nitrobenzene (ENB). Additionally, (co)polyesters containing pendant azido groups were thermally cross-linked (170 degrees C/12 h) leading to the formation of network structures based on azide to nitrene decomposition and subsequent reactions on polyester backbone. The selected cross-linked polyesters were characterized by stress-strain measurements. The cross-linked polymers exhibited higher tensile strength and Young's modulus and lower % elongation at break compared to corresponding pristine polyesters containing pendant azido groups.
Keywords: Aromatic polyester; Chemical modification; Click chemistry; Pendant azido group; Thermal cross-linking

MWCNTs-ZnO-SiO2 mesoporous nano-hybrid materials for CO2 capture - Jena, Kishore K.; Panda, Amulya Prasad; Verma, Savita; Mani, Ganesh Kumar; Swain, S. K.; Alhassan, Saeed M. (Journal of Alloys and Compounds, 2019)
Carbon nanostructures and metal nanoparticles based nanohybrid materials have been established as one of advantageous materials for various applications. Here, we present hydrothermal and sol-gel process at low temperature for the synthesis of (3-Aminopropyl) triethoxysilane (APTES)-ZnO-multi-walled carbon nanotubes (MWCNTs) mesoporous nanohybrid materials. TEM and XPS measurements show that uniform size and quasi-spherical ZnO nanoparticles were anchored to the surface of the MWCNTs. SEM observation exhibits that the aggregation of ZnO nanoparticles is greatly reduced due to the steric repulsion of grafted organic groups. The maximum CO2 adsorption capacity at 273 K was 1.32 mmol/g for MWCNTs-APTES-ZnO-B nanohybrid. An increase in the density of ZnO nanoparticles on the surface of MWCNTs resulted in a higher affinity towards CO2 at low pressure. This work provides new research directions for making further advances toward practical utilization of MWCNTs-based CO2 adsorbents. (C) 2019 Published by Elsevier B.V.
Keywords: CO2 capture; Mesoporous; MWCNTs; Nanohybrid; TEM; XPS

Thermally crosslinkable and chemically modifiable aromatic polyesters possessing pendant propargyloxy groups - Verma, Savita; Maher, Deepak M.; Nagane, Samadhan S.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
New aromatic (co)polyesters containing pendant propargyloxy groups were synthesized by phase transfer-catalyzed interfacial polycondensation of 5-(propargyloxy)isophthaloyl chloride (P-IPC) and various compositions of P-IPC and isophthaloyl chloride with bisphenol A. FTIR and NMR spectroscopic data, respectively, revealed successful incorporation of pendant propargyloxy groups into (co)polyesters and formation of (co)polyesters with desired compositions. (Co)polyesters exhibited good solubility in common organic solvents such as chloroform, dichloromethane, and tetrahydrofuran and could be cast into transparent, flexible, and tough films from chloroform solution. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.77-1.33 dL/g and 43,600-118,000 g/mol, respectively, indicating the achievement of reasonably high-molecular weights. The 10% weight loss temperatures of (co)polyesters were in the range 390-420 degrees C, demonstrating their good thermal stability. (Co)polyesters exhibited T-g in the range 146-170 degrees C and T-g values decreased with increase in mol % incorporation of P-IPC. The study of non-isothermal curing by DSC indicated thermal crosslinking of (co)polyesters via propargyloxy groups. The utility of pendant propargyloxy group was demonstrated by post-modification of the selected copolyester with 1-(4-azidobutyl)pyrene, 9-(azidomethyl)anthracene, and azido-terminated poly(ethyleneglycol) monomethyl ether via copper(I)-catalyzed Huisgen 1,3-dipolar cycloaddition reaction. FTIR and H-1 NMR spectra confirmed that click reaction was quantitative. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 588-597
Keywords: Click chemistry; crosslinking; modification; polyesters; propargyloxy; step-growth polymerization

Antiviral drugs prioritization for COVID-19 management based on rational selection - Joshi, Rakesh S.; Giri, Ashok P.; Kulkarni, Mahesh J.; Gupta, Mahesh; Verma, Savita; Chaudhry, Dhruva; Deshmukh, Narendra; Chugh, Anita (Current Science, 2021)
The SARS-CoV-2 infection has resulted in COVID-19 pandemic worldwide. It has infected around 0.1 billion individuals and caused 2 million fatalities across the globe till mid-January 2021. Drug repurposing has been utilized as the most preferred therapeutic intervention for COVID-19 mitigation due to its necessity and feasibility. To prioritize therapeutic regime against COVID-19, we used 61 antiviral drugs and their combinations. Selected molecules were subjected to virtual screening against: (i) human angiotensin-converting enzyme 2 receptor binding domain (hACE-2) which serves as an anchor for virus attachment and entry, (ii) SARS-CoV-2 RNA dependent RNA polymerase (RdRp) responsible for viral RNA replication, and (iii) SARS-CoV-2 main protease (M-Pro) needed for viral polyprotein slab proteolytic processing. Based on docking score, pharmacodynamic and pharmacokinetic parameters, combinations of Daclatasvir, Elbasvir, Indinavir, Ledipasvir, Paritaprevir and Rilpivirine were analysed further. Our analysis suggested Sofosbuvir in combination with Ledipasvir and Daclatasvir as potential therapeutic agents for SARS-CoV-2. The combined score suggests that these combinations have superior anti-SARS-CoV-2 potential than Remdesivir and other investigational drugs. The present work provides a rationale-based approach to select drugs with possible anti-SARS-CoV-2 activity for further clinical evaluation.
Keywords: Drug repurposing; hACE-2; main protease; RNA dependent RNA polymerase; SARS-CoV-2

Pendant propargyloxy-functionalized aromatic (co)polycarbonates: synthesis, thermal crosslinking and chemical modification - Nagane, Samadhan S.; Maher, Deepak M.; Verma, Savita; Talanikar, Aniket A.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2022)
A bisphenol monomer bearing pendant propargyloxy group viz, 1, 1-bis (4-hydoxyphenyl)-1-(4 `-propargyloxyphenyl) ethane (BPP) was synthesized starting from commercially available 1, 1, 1-tris (4-hydroxyphenyl) ethane (THPE) by mono O-propargylation reaction using propargyl bromide. A new series of pendant propargyloxy-functionalized aromatic (co)polycarbonates was synthesized by low-temperature solution polycondensation of BPP or different molar ratios of BPP and bisphenol-A with triphosgene in dichloromethane in the presence of triethylamine. The formation of reasonably high molecular weight (co)polycarbonates was confirmed by inherent viscosity (0.52-0.83 dL/g) and gel permeation chromatography (M-n 37,000-69,800 g/mol, polystyrene standards) measurements. C-13 NMR spectral studies supported formation of random copolycarbonates in copolymerization of BPP and BPA with triphosgene. The 10% weight loss temperature (T-10) values of (co)polycarbonates, determined by thermogravimetric analysis under nitrogen atmosphere, were in the range 427-438 degrees C indicating their good thermal stability. The glass transition temperature (T-g) values of (co)polycarbonates were observed in the range 147-152 degrees C. The crosslinking ability of (co)polycarbonates involving pendant propargyloxy groups leading to formation of networked structure was evaluated via non-isothermal curing studies by DSC. As a proof-of-concept, the post-modification of a representative polycarbonate bearing pendant propargyloxy groups with 1-octane thiol as a model compound via thiol-yne click reaction was briefly studied.
Keywords: Aromatic polycarbonate; Chemical modification; propargyloxy groups; thermal crosslinking; thiol-yne click reaction

Comprehensive molecular and clinical investigation of approved Anti-HCV drugs repurposing against SARS-CoV-2 infection: a glaring gap between benchside and bedside medicine - Bansode, Sneha; Singh, Pawan Kumar; Tellis, Meenakshi; Chugh, Anita; Deshmukh, Narendra; Gupta, Mahesh; Verma, Savita; Giri, Ashok; Kulkarni, Mahesh; Joshi, Rakesh; Chaudhary, Dhruva (Vaccines, 2023)
The limited availability of effective treatment against SARS-CoV-2 infection is a major challenge in managing COVID-19. This scenario has augmented the need for repurposing anti-virals for COVID-19 mitigation. In this report, the anti-SARS-CoV-2 potential of anti-HCV drugs such as daclatasvir (DCV) or ledipasvir (LDP) in combination with sofosbuvir (SOF) was evaluated. The binding mode and higher affinity of these molecules with RNA-dependent-RNA-polymerase of SARS-CoV-2 were apparent by computational analysis. In vitro anti-SARS-CoV-2 activity depicted that SOF/DCV and SOF/LDP combination has IC50 of 1.8 and 2.0 mu M, respectively, comparable to remdesivir, an approved drug for COVID-19. Furthermore, the clinical trial was conducted in 183 mild COVID-19 patients for 14 days to check the efficacy and safety of SOF/DCV and SOF/LDP compared to standard of care (SOC) in a parallel-group, hybrid, individually randomized, controlled clinical study. The primary outcomes of the study suggested no significant difference in negativity after 3, 7 and 14 days in both treatments. None of the patients displayed any worsening in the disease severity, and no mortality was observed in the study. Although, the post hoc exploratory analysis indicated significant normalization of the pulse rate showed in SOF/DCV and SOF/LDP treatment vs. SOC. The current study highlights the limitations of bench side models in predicting the clinical efficacy of drugs that are planned for repurposing.
Keywords: antiviral; COVID-19; daclatasvir; ledipasvir; SARS-CoV-2; sofosbuvir